The Effect of Administering Kelor Flower (Moringa Oleifera) Extract on Reducing Cholesterol Levels and Histopathological Features of The Testis of White Rats (Rattus norvegicus) Male Wistar Strain Obesity - Irawan, Muhammad Andi; Tarigan, Antje Irmella; Dalimunthe, Siti Aisyah (PT Inovasi Pratama Internasional, 2024)
Obesity and high cholesterol levels have garnered clinical attention for male infertility. The numerous compounds in Kelor flowers or Moringa make it a potential cholesterol medication. The research data were analyzed using SPSS, and the study was conducted as a true experiment using test animal samples of twenty-four male Wistar rats (Rattus norvegicus). The purpose of this study was to examine the histopathological features of obese male Wistar rats (Rattus norvegicus) and to determine whether or not the administration of Kelor flower extract (Moringa ternatea) reduced cholesterol levels and improved testicular function. Obese white Wistar rats had their total cholesterol levels decreased by 400 mg/kgBW and 600 mg/kgBW of Kelor flower extract, respectively, according to the study's results. The group that received 600 mg/kgBW of Kelor flower extract showed the most improvement and was the most similar to the control group in testicular histopathology studies. The substances found in Kelor or Moringa flowers have been found to improve testicular function and lower total cholesterol levels in people who suffer from obesity, according to the research.